PENGHAYATAN IDENTITAS GENDER PADA PEREMPUAN KARIR SUKU BATAK TOBA SUMATERA UTARA - Desi Ananta Sari Ketaren (Jurnal Inovasi Penelitian, 2023)
Gender identity is self-concept which implicates the identification of someone as man or woman (Baron & Bryne, 2004). Gender is the characteristic of someone’s personality and influenced by his/her gender role The Batak Toba Tribe has the traditions and cultures that are unique and different to other cultures in Indonesia. One of them is the role of men is higher than women. In modern era nowadays, whereas, there are women who choose to be a career women in which makes their existence as women is higher than men. This leads to the question of how the women in Batak Toba Tribe live the gender identity in their family observed in the aspect of access, participation, control, and benefit that they have as career women. The purpose of this study was to the appreciation of gender identity in Toba Batak career women in North Sumatra. The method used is qualitative approach with observation and interview in data collection technique. The result of the research shows that the life of gender identity of women in Batak Toba Tribe in their household live is similar from the aspect of access side, yet the burden is bigger. Whereas, the participation, control, and benefit side of women in Batak Toba Tribe is less in the occasion to take decisions of the household. The conclusion from the research results is that there is inequality in the appreciation of gender identity in career women of the Batak Toba tribe